PRESSURE EFFECT OF TI- OR P-RICH ACCESSORY MINERAL SATURATION IN EVOLVED GRANITIC MELTS WITH DIFFERING K2O/NA2O RATIOS - Green T.H.; Adam J. (My University, 2002)
The solubility of Ti- and P-rich accessory minerals has been examined as a function of pressure and K2O/Na2O ratio in two series of highly evolved silicate systems. These systems correspond to (a) alkaline, varying from alkaline to peralkaline with increasing K2O/Na2O ratio; and (b) strongly metaluminous (essentially trondhjemitic at the lowest K2O/Na2O ratio) and remaining metaluminous with increasing K2O/Na2O ratio (to 3). The experiments were conducted at a fixed temperature of 1000 °C, with water contents varying from 5 wt.% at low pressure (0.5 GPa), increasing through 5–10 wt.% at 1.5–2.5 GPa to 10 wt.% at 3.5 GPa. Pressure was extended outside the normal crustal range, so that the results may also be applied to derivation of hydrous silicic melts from subducted oceanic crust.